Association of β-Lactam Allergy Documentation and Prophylactic Antibiotic Use in Surgery: A National Cross-Sectional Study of Hospitalized Patients. (26th November 2020) - Bertram, Christie M; Postelnick, Michael; Mancini, Christian M; Fu, Xiaoqing; Zhang, Yuqing; Schulz, Lucas T; Bhowmick, Tanaya; Lee, Francesca; Blumenthal, Kimberly G
Abstract: Alternative antibiotics for surgical prophylaxis are associated with increased adverse events and surgical site infection compared to cefazolin. In a sample of perioperative inpatients from 100 hospitals in the United States, cefazolin was 9-fold less likely to be used in patients with a documented β-lactam allergy whereas clindamycin was 45-fold more likely.